Analisis Makna Kebebasan J.S. Mill pada Manusia dalam Berhadapan dengan Protokol Kesehatan pada Masa Pandemi Covid-19 - Muhamad Faturrohman (Jurnal Riset Agama, 2022)
One of the recommendations to minimize the spread of the Covid-19 virus is by implementing health procedures, such as wearing masks, washing hands, maintaining distance, avoiding crowds, and reducing mobility. However, the application of this process raises a philosophical question regarding the meaning of human freedom, namely whether this process limits or hinders human freedom and how to critically examine the meaning of human freedom during a pandemic in the face of the Covid-19 health protocol. This paper includes a literature study, using qualitative methods, and John Stuart Mill's theory of robustness as an analytical knife. The findings in this paper are that first, health protocols must be understood as an effort to prevent the spread of related viruses and to save lives and protect human survival. This must be used as a basis for awareness for the common good. Second, the community in dealing with Covid-19 has expressed its freedom integrally. In this pandemic situation, if he wants to achieve his life goals, a collective awareness is needed, in which he cannot be selfish and only fight for his own freedom. However, it is also the freedom of others, which he must protect and respect.